2010
DOI: 10.5152/akd.2010.137
|View full text |Cite
|
Sign up to set email alerts
|

An important role for VCAM-1, but not for ICAM-1 in restenosis following coronary stent implantation

Abstract: Amaç: Bu çalışmada stabil koroner arter hastalığı nedeni ile stent implante edilen olgularda, adezyon moleküllerinin seviyesi ile restenoz arasındaki ilişki araştırılmıştır. Yöntemler: Stabil angina pectoris nedeni ile proksimal sol ön inen artere stent implante edilen 15 olguda işlem öncesi ve sonrasında dolaşım-daki hücreler arası adezyon molekül-1 (ICAM-1) ve vasküler hücre adezyon molekül -1 (VCAM-1) seviyeleri prospektif gözlemsel olarak araştı-rılmıştır. Hastalarda çıplak metal stent kullanılmıştır. Tüm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…Vascular cell adhesion molecule-1 (VCAM-1) is an immunoglobulin superfamily-specific receptor that provides high-affinity interactions between ECs and integrins on the leukocyte surface and facilitates transendothelial migration [10,13,14]. Moreover, VCAM-1 binds with monocytes, but not neutrophils, and it is the first CAM expressed in chronic inflammation such as atherosclerosis (before atherosclerotic plaque development) [13,14,24] and restenosis following coronary stent implantation [25]. Thus, VCAM-1 can be used as an indicator of in vitro EC activation during the early stages of inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…Vascular cell adhesion molecule-1 (VCAM-1) is an immunoglobulin superfamily-specific receptor that provides high-affinity interactions between ECs and integrins on the leukocyte surface and facilitates transendothelial migration [10,13,14]. Moreover, VCAM-1 binds with monocytes, but not neutrophils, and it is the first CAM expressed in chronic inflammation such as atherosclerosis (before atherosclerotic plaque development) [13,14,24] and restenosis following coronary stent implantation [25]. Thus, VCAM-1 can be used as an indicator of in vitro EC activation during the early stages of inflammation.…”
Section: Introductionmentioning
confidence: 99%
“… 24 In addition to atherosclerotic plaque formation, adhesion molecules might also be involved in the generation of restenotic neointima. 25 VCAM-1 was overtly upregulated in neointimal smooth muscle cells in an animal model of wire-induced vascular injury. 26 In genetically hypercholesterolemic mice, VCAM-1 antibodies protect from neointima generation.…”
Section: Discussionmentioning
confidence: 92%
“…Inflammation is not only central to the pathogenesis of atherosclerosis and plaque instability, but also contributes to adverse clinical outcomes related to PCI . A growing body of clinical research has demonstrated that circulating inflammatory markers (VCAM‐1, ICAM‐1, MCP‐1, IL‐6 and CRP) are strong predictors for mortality and future cardiovascular events in many clinical settings, including ACS patients following PCI . Previous studies have reported that berberine can inhibit the expression of tumour necrosis factor‐α, MCP‐1, IL‐6 and cyclo‐oxygenase‐2 in stimulated macrophages by activating AMP kinase or inhibiting extracellular signal‐regulating kinase (ERK) 1/2 .…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7]21 A growing body of clinical research has demonstrated that circulating inflammatory markers (VCAM-1, ICAM-1, MCP-1, IL-6 and CRP) are strong predictors for mortality and future cardiovascular events in many clinical settings, including ACS patients following PCI. [22][23][24][25][26] Previous studies have reported that berberine can inhibit the expression of tumour necrosis factor-a, MCP-1, IL-6 and cyclo-oxygenase-2 in stimulated macrophages by activating AMP kinase or inhibiting extracellular signal-regulating kinase (ERK) 1/2. 16,17,19 In the present study, we found that berberine treatment for 30 days decreased circulating levels of several inflammatory markers, namely VCAM-1, ICAM-1 and MMP-9, in ACS patients after PCI.…”
Section: Discussionmentioning
confidence: 99%